2011
DOI: 10.1080/15538605.2011.633157
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar and Queer: Spiritual and Emotional Salvation for the LGBTQ Mormon

Abstract: Clients who are lesbian, bisexual, gay, transgendered, or queer (LBGTQ) and members or former members of The Church of Jesus Christ of Latter-day Saints (sometimes referred to as the Mormon or LDS Church) face a distinctive spiritual conundrum. Often people see LDS members as having "peculiar" beliefs. These "peculiar" beliefs and the social system of the Latter-day Saints distinguish them from other forms of Christianity, and create a paradigm of conflict for those who do not fit in the mold of the Mormon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Because of the LDS church’s strong stance toward same-sex sexuality and the resistance of sexual orientation to change (Beckstead & Morrow, 2004), individuals may feel pressure to disavow either their sexual identity or religious identity to maintain a sense of cognitive consistency (Dehlin et al, 2015a; Jacobsen & Wright, 2014). It is likely that those who were “caught between” identities reported less well-being due to dissonance between their sexual and religious identities (Crowell, Galliher, Dehlin, & Bradshaw, 2015; Dahl & Galliher, 2012; Festinger, 1957; Hamblin & Gross, 2013; Johns & Hanna, 2012). Those who report a strong Mormon or LGBQ identity may also benefit from a stronger sense of community associated with their identity (Dehlin et al, 2015a; Hamblin & Gross, 2013; Joseph & Cranney, 2017; Lefevor, Sorrell, et al, 2019; Nielson, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the LDS church’s strong stance toward same-sex sexuality and the resistance of sexual orientation to change (Beckstead & Morrow, 2004), individuals may feel pressure to disavow either their sexual identity or religious identity to maintain a sense of cognitive consistency (Dehlin et al, 2015a; Jacobsen & Wright, 2014). It is likely that those who were “caught between” identities reported less well-being due to dissonance between their sexual and religious identities (Crowell, Galliher, Dehlin, & Bradshaw, 2015; Dahl & Galliher, 2012; Festinger, 1957; Hamblin & Gross, 2013; Johns & Hanna, 2012). Those who report a strong Mormon or LGBQ identity may also benefit from a stronger sense of community associated with their identity (Dehlin et al, 2015a; Hamblin & Gross, 2013; Joseph & Cranney, 2017; Lefevor, Sorrell, et al, 2019; Nielson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2013; Johns & Hanna, 2012). Those who report a strong Mormon or LGBQ identity may also benefit from a stronger sense of community associated with their identity (Dehlin et al, 2015a;Hamblin & Gross, 2013;Joseph & Cranney, 2017;Lefevor, Sorrell, et al, 2019;Nielson, 2016).…”
Section: Understanding Religiousness Among Sexual Minority Mormonsmentioning
confidence: 99%
“…Although identity development of queer individuals in R/S contexts has traditionally been explored without examining identity intersections (Bozard & Sanders, 2011), scholars have begun to identify contextual influences on identity development (Dillon et al, 2011) and have begun noting the difficulty of simultaneously identifying as queer and R/S (Barton, 2010; Beagan & Hattie, 2015; Bozard & Sanders, 2011; Crockett et al, 2018; Dahl & Galliher, 2009; Dillon et al, 2011; McGlasson & Rubel, 2015; Rodriguez, 2009; Sherry et al, 2010; Super & Jacobson, 2011). Multiple scholars have provided valuable insight into conceptualization practices and counseling interventions for individuals who wish to embrace and integrate these disparate identities, including the following: influence of R/S abuse (e.g., Super & Jacobson, 2011; Wood & Conley, 2014), process of negotiation and integration (e.g., Ginicola & Smith, 2011; Heard Harvey & Ricard, 2018; Johns & Hanna, 2011; Rosik & Popper, 2014; Yarhouse & Beckstead, 2011), development of conceptual frameworks (e.g., Kocet et al, 2011; Shurts et al, 2020), treatment approaches (e.g., Bayne, 2016; Bozard & Sanders, 2011; Hagen et al, 2011; Suprina et al, 2019), and use of cognitive theories (e.g., Anderton et al, 2011; V. R. F. Johnson & Yarhouse, 2013; Rodriguez, 2009).…”
Section: Negotiating and Integrating Queer And Religious/spiritual Identitiesmentioning
confidence: 99%
“…Themes emerged from interviews with gay fathers in each context, broadly summarized in Table 1, that reflect differences in the religious backgrounds of gay fathers, emotions that accompany gay fatherhood, gay fathers' geography, and gay fathers' relationship to the closet. Christ of Latter-Day Saints (LDS) has been famously reluctant to affirm gay and lesbian relationships (Dehlin et al, 2015;Johns & Hanna, 2011). A large study of 1,612 same-sex attracted members of the LDS Church found many negative outcomes -including depression, internalized homophobia, poor quality of life, failed conversion therapy attempts, and divorceassociated with anti-LGB beliefs and practices common to the modern LDS Church (Bradshaw et al, 2015;Crowell et al, 2014;Dehlin et al, 2014;Dehlin et al, 2015).…”
Section: Characteristics Of the Normal Gay Fathermentioning
confidence: 99%